Evidence for an enhanced procoagulant state in remitted major depression. (25th November 2020) - von Känel, Roland; Merz, Franziska; Pfister, Hildegard; Brückl, Tanja; Zimmermann, Petra; Uhr, Manfred; Holsboer, Florian; Höhne, Nina; Ising, Marcus
Abstract: Objectives: Hypercoagulability is one mechanism to explain the increased risk of incident atherothrombotic disease in patients with major depressive disorder (MDD). We examined whether patients with remitted MDD show an enhanced procoagulant state. Methods: 63 individuals (median age 35 years, 59% women), 40 with a DSM-IV diagnosis of remitted MDD, made by a clinical interview, and 23 healthy controls provided blood samples for the measurement of fibrinogen, D-dimer, von Willebrand factor, and plasminogen activator inhibitor-1. Standardised z -scores of plasma levels of these haemostatic factors were added to form a procoagulant index (PCI) as the primary outcome variable. Self-ratings of residual depressive symptoms and trait anxiety were also obtained. Results: Compared with controls, remitted MDD patients had higher PCI ( p = 0.013, Cohen's d = 0.69) and fibrinogen ( p = 0.001, d = 0.91), controlling for age, sex, body mass index, smoking and C-reactive protein. There were no significant associations of the PCI and individual haemostatic molecules with age of MDD onset, time since the last MDD episode, the number of previous MDD episodes and residual depressive symptoms. Additional adjustment for anxiety symptoms did not change these results. Conclusions: Remitted MDD is associated with an enhanced procoagulant state. Hypercoagulability seems more a trait than a state characteristic of depression.